Advertising economics under uncertainty: An alternative approach - James P. Gander (The University of Utah, Department of Economics, 2018)
The purpose of this paper is to present an alternative approach to analyzing firm advertising under uncertainty. The approach considers the simultaneity (or duality) of two effects of advertising, one effect on the probability associated with the bundle of goods the typical buyer purchases and the other effect on the probability associated with the time the buyer spends in the store making the purchases. While bundle and time are well explored in the literature, our simultaneity approach to determine the optimum level (and type) of advertising results in implications that are not present in the literature. The novelty of this alternative approach is that it shows that there can be the possibility of an equivalent dual optimal advertising effect on the expected value of the bundle and the expected value of the time spent. The implications of such an equivalence (or lack thereof) for advertising decision making are then explored.
Keywords: 330; Advertising; Uncertainty; Bundle; Time Spent; Equivalence